2004
DOI: 10.1097/01.ccm.0000132899.15242.d3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α is associated with early postresuscitation myocardial dysfunction

Abstract: Tumor necrosis factor-alpha increases during the early postresuscitation period and may play a role in postresuscitation myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…6-8 Laboratory investigations confirm that activation of proinflammatory cytokine pathways is evident early after resuscitation from cardiac arrest. 9,10 Studies in animal models, primarily rodents, and in the clinical population, including both healthy and injured people, suggest that there are gender differences in the cytokine response to stress. 11-16 In animal models, males appear to be more likely to develop sepsis than females and females have a lower mortality rates than males.…”
Section: Introductionmentioning
confidence: 99%
“…6-8 Laboratory investigations confirm that activation of proinflammatory cytokine pathways is evident early after resuscitation from cardiac arrest. 9,10 Studies in animal models, primarily rodents, and in the clinical population, including both healthy and injured people, suggest that there are gender differences in the cytokine response to stress. 11-16 In animal models, males appear to be more likely to develop sepsis than females and females have a lower mortality rates than males.…”
Section: Introductionmentioning
confidence: 99%
“…Following ROSC, various pathophysiological disturbances are observed as post-resuscitation syndrome (1). Post-resuscitation syndrome is the greatest ischemia-reperfusion injury in humans and is recognized as microcirculation impairment and tissue damage in many vital organs (1)(2)(3)(4)(5)(6). The microcirculation impairment and tissue damage after reperfusion may affect the neurological outcome and prognosis in patients following cardiac arrest (2-7).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor-TNF) plays the most significant role in regulating the ischemia-reperfusion molecular NE = neutrophil elastase ROSC = return of spontaneous circulation SOFA = Sequential Organ Failure Assessment TNF- = tumor necrosis factor- UTI = urinary trypsin inhibitor 5 pathway (6,8). The increase in TNF-contributes to cell death, apoptosis, and several organ dysfunctions (6). Endothelial adhesion molecules induce neutrophil accumulation both within the microvessels and extravascular tissues (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo overall increase of the amount of TNF-can decrease cardiac output, and then mediates tissue injury, such as formation of microthrombus and systemic capillary leak syndrome. As to regulating molecular pathway of the ischemia-reperfusion, TNF-maybe one of the most significant factors (Niemann, Garner and Lewis 2004;Toledo-Pereyra et al 2004). At the same time, TNF-can also through activating other related cells secret cytokine such as IL-1, HMGB1, eicosanoids, NO, and reactive oxygen to enhance the role of inflammatory reaction and make this effect longer www.intechopen.com (Tracey 2002).…”
Section: Inhibit Releasing Of Tnf-α To Act As Protective Actionmentioning
confidence: 99%
“…It was found that serum TNFsignificantly elevated during the septic systemic inflammatory response syndrome (SIRS) (Kurt et al 2007). In all , TNF-can promote occurrence and development of the sepsis, the level of TNF-increasing can lead to cell death, apoptosis, and several organs dysfunction (Niemann, Garner and Lewis 2004). Thus it is very important to inhibit the release of TNF.…”
Section: Inhibit Releasing Of Tnf-α To Act As Protective Actionmentioning
confidence: 99%